New therapeutic approach for intestinal fibrosis through inhibition of ph-sensing receptor GPR4 - Weder, Bruce; Schefer, Fabian; van Haaften, Wouter Tobias; Patsenker, Eleonora; Stickel, Felix; Mueller, Sebastian; Hutter, Senta; Schuler, Cordelia; Baebler, Katharina; Wang, Yu; Mamie, Céline; Dijkstra, Gerard; et al. (Inflammatory bowel diseases, 2022)
Patients suffering from inflammatory bowel diseases (IBDs) express increased mucosal levels of pH-sensing receptors compared with non-IBD controls. Acidification leads to angiogenesis and extracellular matrix remodeling. We aimed to determine the expression of pH-sensing G protein-coupled receptor 4 (GPR4) in fibrotic lesions in Crohn’s disease (CD) patients. We further evaluated the effect of deficiency in Gpr4 or its pharmacologic inhibition.Paired samples from fibrotic and nonfibrotic terminal ileum were obtained from CD patients undergoing ileocaecal resection. The effects of Gpr4 deficiency were assessed in the spontaneous Il-10-/- and the chronic dextran sodium sulfate (DSS) murine colitis model. The effects of Gpr4 deficiency and a GPR4 antagonist (39c) were assessed in the heterotopic intestinal transplantation model.In human terminal ileum, increased expression of fibrosis markers was accompanied by an increase in GPR4 expression. A positive correlation between the expression of procollagens and GPR4 was observed. In murine disease models, Gpr4 deficiency was associated with a decrease in angiogenesis and fibrogenesis evidenced by decreased vessel length and expression of Edn, Vegfα, and procollagens. The heterotopic animal model for intestinal fibrosis, transplanted with terminal ileum from Gpr4-/- mice, revealed a decrease in mRNA expression of fibrosis markers and a decrease in collagen content and layer thickness compared with grafts from wild type mice. The GPR4 antagonist decreased collagen deposition. The GPR4 expression was also observed in human and murine intestinal fibroblasts. The GPR4 inhibition reduced markers of fibroblast activation stimulated by low pH, notably Acta2 and cTgf.Expression of GPR4 positively correlates with the expression of profibrotic genes and collagen. Deficiency of Gpr4 is associated with a decrease in angiogenesis and fibrogenesis. The GPR4 antagonist decreases collagen deposition. Targeting GPR4 with specific inhibitors may constitute a new treatment option for IBD-associated fibrosis.
Online veröffentlicht: 28. Juli 2021
Gesehen am 25.10.2022